2014
DOI: 10.1186/1472-6750-14-85
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of a new β-Glucosidase from a metagenomic library of Rumen of cattle feeding with Miscanthus sinensis

Abstract: BackgroundThe study on the second generation bio-fuel is a hot area of current research of renewable energy. Among series of key points in this area, the role of β-glucosidase in the degradation of intermediate gluco-oligosaccharides limits the rate of the complete saccharification of lignocellulose.ResultsIn this study, a new β-glucosidase gene, unglu135B12, which was isolated from a metagenomic library of rumen of cattle feeding with Miscanthus sinensis by the function-based screening, encodes a 779 amino ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 30 publications
3
18
0
1
Order By: Relevance
“…The unique properties of Cen502 are summarized as follows: Cen502 is characterized by high catalytic efficiency at high pH, as indicated by its optimum enzymatic activity at pH 8.0. The optimum pH of purified Cen502 was higher than most known β-glucosidases, which typically exhibit optimal pHs below 7.0 13 , 15 , 22 25 . Of note, Cen502 is active over a wide range of pHs, retaining 56% of its activity at pH 9.0, and is stable over the pH range 5.0–9.0.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The unique properties of Cen502 are summarized as follows: Cen502 is characterized by high catalytic efficiency at high pH, as indicated by its optimum enzymatic activity at pH 8.0. The optimum pH of purified Cen502 was higher than most known β-glucosidases, which typically exhibit optimal pHs below 7.0 13 , 15 , 22 25 . Of note, Cen502 is active over a wide range of pHs, retaining 56% of its activity at pH 9.0, and is stable over the pH range 5.0–9.0.…”
Section: Discussionmentioning
confidence: 81%
“…The β-glucosidase from Fusarium oxysporum has optimal activity at pH 5.0, and the enzyme is stable over the pH range 4.0–7.0 24 . Likewise, the optimal pH of the β-glucosidase Unglu135B12 from cattle rumen is 5.0, and the enzyme is stable only in the pH range 5.0–6.0 25 . The β-glucosidase Ho BGLA from Halothermothrix orenii has maximal activity at pH 6.0 and is stable in the pH range 4.5–7.5 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Most bioconversion is focused on the production of a sugar platform of simple sugars which can then biologically or chemically be converted into fuels (e.g., ethanol, butanol and hydrocarbons) (Cherubini 2010 ). Recently, Li et al ( 2014 ) cloned and characterized a β-glucosidase from rumen microbes of cattle feeding with Miscanthus sinensis and this plant is used as an ideal source of biofuel. Coating of β-glucosidase on polymer nanofibers was also found more efficient for cellulosic ethanol production (Lee et al 2010 ).…”
Section: Industrial Application Of β-Glucosidasesmentioning
confidence: 99%
“…Hong et al (2006) have found that an enzyme with both b-glucosidase and bxylosidase activity showed a better cellulolytic efficiency. Li et al (2014) have found in ruminal microorganisms from B. taurus a novel b-glucosidase gene, which encodes for a protein, unglu135B12, with a molecular weight of 84.1 kDa. This protein has an optimal reaction temperature of 38∞C and an optimal pH of 5.0 and shows the highest similarity with proteins from Bacteroidetes.…”
Section: Discussionmentioning
confidence: 99%